Engaging Persia in the Former Soviet Union. - Latimer, Michael R. (Tufts Archival Research Center, 2014)
Abstract: "Engaging Persia in the Former Soviet Union" analyzes how American-Iranian interests converge and diverge in Central Asia. Specifically, it focuses on the stability of Afghanistan and the diversification of Central Asian energy economies via Iranian participation in Caspian energy projects. At the height of Soviet prominence, the Soviets monopolized Central Asian energy economies by constructing pipelines that were reliant on Russian transit routes to Europe. After the collapse of the Soviet Union, American policy in the region failed to promote the independence of Central Asia and Azerbaijan by hindering the diversification of Central Asian and Azerbaijani energy economies. Instead, the United States pursued a policy to prioritize the economic and political development of Russia while simultaneously containing Iran. By barring Iranian participation in Caspian Energy projects, America prevents competition and empowers Russian influence in Central Asia. The essay discusses the competing interests of all the major powers in Central Asia (China, Russia, India, Turkey, Iran, America) before exploring how American-Iranian interests converge and diverge in the region. Next, the essay explains how Iranian participation in Caspian energy projects will counter Russian imperialism and mitigate China's rise in the region, thus benefiting American interests. Despite mutual interests, the argument acknowledges and rectifies potentially divergent interests in the Persian Gulf and Central Asia. Next, the thesis identifies the obstacles to a feasible American policy in the region, namely the Saudi and Israeli lobbies. In conclusion, the thesis provides a prescription for a new American policy in the region and discusses the implications of this new approach.